Stipulating citizen's fundamental right to healthcare: Inference from the Constitution of Federal Republic of Nepal 2015 - Simkhada, Padam; Regmi, Pramod R; Pant, Puspa Raj; van Teijlingen, Edwin; Sathian, Brijesh (Nepal Journal of Epidemiology, 2015)
Nepal has a great opportunity to learn from, and collaborate with, non-governmental development partners and private sectors, and from other governments and organizations around the world, but we must move promptly.